INTERNATIONAL CONVENTIONS ON THE TRANSPORT OF GOODS AND ELECTRONIC TRANSPORT DOCUMENTS - Divljak, Drago (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
The regulatory approach of international conventions on the transport of goods regarding some important issues in the field of electronic transport documents, such as the legal recognition of electronic transport documents, their functions and legal force makes the subject of analysis in this paper. The overall reach and limitations of the relevant convention rules are also included in the analysis. Conventions in the field of transport of goods, neither conceptually nor in terms of important issues, do not approach the problem of legal regulation of electronic transport documents in the same manner. While some conventions try to approach this problem systematically, in some branches of transport, the conventions are still applicable which, with their content, only implicitly enable the use of electronic transport documents. Regarding the completeness of the regulation of this matter, the Rotterdam Rules and the Additional Protocol to the CMR Convention stand out, but they differ in terms of the adequacy of regulation and final reach. The Rotterdam Rules, despite a very ambitious approach, have failed to adequately resolve the most challenging issue of this entire matter, which is the effective accomplishing of the subject matter-legal functions of a portable electronic record, which greatly reduced its ultimate reach. On the other hand, the Additional Protocol established a completely satisfactory legal foundations for the application of electronic transport documents in road transport.
Keywords: international conventions, transport of goods, electronic transport documents, legal recognition, accomplishing of functions.